Comparison of centralized and decentralized air-conditioning systems for a multi-storey/multi users building integrated with electric and diesel vehicles and considering the evolution of the national energy system. (15th June 2019) - Marrasso, E.; Roselli, C.; Sasso, M.; Tariello, F.
Abstract: In this paper four different air conditioning systems designed for a building located in Naples, are investigated. The first plant is based on distributed energy conversion systems: twelve boilers and twelve chillers. In the second solution the space heating demand is satisfied by a centralised boiler while the cooling load is met by a centralised chiller. The third option consists of a trigeneration plant. The fourth configuration is composed by an electric heat pump satisfying space heating and cooling and a centralised boiler used for domestic needs. Dynamic simulations have been carried out to compare the energy and environmental performance of the centralised systems with those achieved by the distributed one. Besides, as further loads, for the third option, two electric vehicles charged by the cogenerated electricity surplus are compared to diesel cars. The results show that the best energy and environmental performance are achieved by the cogenerator-based system, with a primary energy demand of 120.6 MWh/y and equivalent dioxide carbon emissions of 25.2 t/y in the configuration without vehicles. This result is also confirmed with electric and diesel vehicles. The energy competitiveness of the plant with the electric heat pump is achieved only in a scenario with a high penetration of renewable energy sources. Highlights: Autonomous and centralised air conditioning systems are compared. Dynamic simulations are performed to carry out energy and environmental analyses. A multi-purpose block of flats is considered as users simulated. Electric and diesel vehicles are introduced in the analysis. A sensitivity analysis is carried out considering the renewable energy sources contribution.